Identification of 9-oxo-1, 2, 3, 4, 5, 6, 10, 19-octanor-13, 17-secoandrost-8(14)-ene-7, 17-dioic acid as a metabolite of steroid degradation in Comamonas testosteroni TA441 and the genes involved in the conversion. Issue 185 (January 2019) - Horinouchi, Masae; Koshino, Hiroyuki; Malon, Michal; Hirota, Hiroshi; Hayashi, Toshiaki
Highlights: Metabolites of steroids with only C-ring were identified from Comamonas testosterone . 9-Oxo-1, 2, 3, 4, 5, 6, 10, 19-octanor-13, 17-secoandrost-8(14)-ene-7, 17-dioic acid was isolated. ORF1 and 2-encoded-CoA-transferase (ScdL1L2) converts CoA-ester of this compound. Abstract: Comamonas testosteroni TA441 degrades steroid compounds via aromatization of the A-ring to produce 9, 17-dioxo-1, 2, 3, 4, 10, 19-hexanorandrostan-5-oic acid (a metabolite with C- and D-rings), which is presumed to be further degraded via β-oxidation. In elucidating the complete steroid degradation process in C. testosteroni, we isolated 9-oxo-1, 2, 3, 4, 5, 6, 10, 19-octanor-13, 17-secoandrost-8(14)-ene-7, 17-dioic acid and several other metabolites containing only C-ring. For conversion of the CoA-ester of this compound, a two-subunit β -ketoacyl-CoA-transferase encoded by ORF1 and ORF2 was shown to be indispensable. ORF1 and ORF2 are located just after tesB, the meta -cleavage enzyme gene in one of the two major steroid degradation gene clusters of strain TA441. Conversion by the CoA-transferase leads to cleavage of the remaining C-ring, and the product was suggested to be further degraded by β-oxidation involving other genes in the cluster. ORF1 and ORF2 are considered orthologues of ipdAB gene in Mycobacterium tuberculosis H37Rv, which is recently reported as the CoA-transferase of 9-oxo-1, 2, 3, 4, 5, 6, 10, 19-octanor-13, 17-secoandrost-8(14)-ene-7, 17-dioic acid (Crowe AM, Casabon I, Brown KL, Liu J, Lian J, Rogalski JC, Hurst TE, Snieckus V, Foster LJ, Eltis LD. 2017. MBio 8).